Working capital management and firm profitability during and after the economic crisis among Malaysian listed companies - Kademi, Tasiu Tijjani (2014)
The aim of the study is to explore the working capital management components and examine their relationship with firm profitability among Malaysia listed companies during and after the global financial crisis of 2008-2009. Based on the descriptive results, Malaysian firms practice conservative working capital management techniques due to the fact that current ratio is high and debt ratio is low compared with prior studies.The multiple regression analysis on the 260 listed Bursa Malaysia companies shows a negative relationship between working capital management components (i.e. average collection period and average payment period) and firm profitability during and after the crisis periods. Moreover, cash conversion cycle negatively relates with firm profitability after the crisis. Inventory turnover days indicate a positive and significant relation with firm profitability during the crisis period. These findings suggest that Malaysian firms should try and collects cash from customers faster, pay bills as soon as possible and minimise the gap between initial investment and the time cash is collected from customers during both crisis and noncrisis periods. Nevertheless, management should maintain considerable level of stock to avoid shortage and supply interruption during the crisis